Terminology – a new direction in science (Eurasian Journal of Philology Science and Education, 2016)
This article is devoted to some problems of terminology, as a new branch of science. The author of article presents some of the scientific problems of terminology. It reveals the essence of the scientific ideas of scientists like A.V.Superanskaya, Sh.Kurmanbayuly and others. The author reveals the link between terminology and vocabulary of literary language as the national language of the two formulations in the article. In the article the author also talks about the process deinternatsionalization which clearly manifested recently in the problem of terminology.
Keywords: professional vocabulary; terminology; science of terminology; literary language; national language; deinternatsionalization.